Pengaruh Perendaman Air Kelapa Dan Rootone F Terhadap Pertumbuhan Stek Tanaman Nilam (Pogstemon cablin, Benth) - Irwanto Irwanto; Rustam Baraq Noor; Abdul Rofik (Agrifarm : Jurnal Ilmu Pertanian, 2019)
This study aims to determine the growth rate of patchouli (Pogostemon cablin, Benth) with f rotoone administration and coconut water. The research was conducted on land peraktek Polytechnic State Agricultural Samarinda time for 2 months starting from the month of June to August 2016. The research design used was completely randomized design (CRD) with 6 treatments and 6 replications. treatment is a0 = control, a1 = Immersion Coconut Water with a concentration of 50% pure coconut water, a2 = Immersion Coconut Water with a concentration of 100% pure coconut water, a3 = Immersion Rootone F with a concentration of 50 grams, a4 = basting mixture Coconut Water 50% with a mixture of 50 grams Rootone F, basting mixture a5 = 100% Coconut Water with a mixture Rootone F 50 grams. Results of analysis of variance showed that the Effects of Immersion Water Oil And Rootone F on Growth Cuttings Plant Patchouli (Pogostemon cablin, Benth) a very significant effect on the number of shoots 2 weeks after planting, plant height 2 WAP, 6 WAP, stem diameter 2 WAP, 4 WAP, 6 WAP and 8 WAP. real effect on the number of parameters shoots 4 WAP, 6 WAP, 8 WAP, plant height 4 and 8 WAP.